Automated Monitoring System for the Fish Farm Aquaculture Environment - Jui-Ho Chen; Wen-Tsai Sung; Guo-Yan Lin (2015 IEEE International Conference on Systems, Man, and Cybernetics, 2015)
This panel will establish an automated monitoring system of wireless sensor networks for a fish farm Environment Simulation. This system allows a user with a mobile device to monitor the fish farm Environmental Data with Instant mastery and control over the various environmental data. Temperature, dissolved oxygen, PH value and water level sensing modules are incorporated in this monitoring system. MCU processing is used to capture the physical sensing signal. The ZigBee wireless sensor network brings the data to a central processing core. A WIFI interface transfers the data to the user terminal device. The user can control the entire fish farm environment through the terminal device. Android software was used to design the terminal device user interface. A low power MSP430 series MCU is the core of each sensing terminal and the central terminal. The power supply can be battery-powered, standard electricity supply and/or solar battery powered. UPS makes the whole system more secure with low-cost, low energy consumption, easy operating features with a high degree of freedom for this wireless breeding environment monitoring system.